The Development, Validation, and Generalizability of the Technological Adaptive Expertise Scale - Tran, Phuoc (My University, 2017)
Technology is rapidly changing and with it the need for the ability to adapt to change increases. Whether consciously or unconsciously, users of technology may have developed varying degrees of technological adaptability. Our study develops a scale to measure this trait referred to as Technological Adaptive Expertise (TAE). We conducted the scale development in three studies, the first preliminary study established a factor structure, the second study tested replication and explored retrospective estimates of outcomes, the third study assessed generalizability to an online open sample. Three factors were replicated: Technical metacognition, troubleshooting and use of Trial and error, average fit indices were RMSEA = .078, GFI = .787, CFI = .755. The Retrospective estimates scale was a 2-factor measure split between positive and negative outcomes, mean fit indices were RMSEA = .121, GFI = .58, CFI = .608. Reducing the number of items for each factor resulted in improved fit. Technical metacognition was associated with significantly greater positive (r = .18) and less negative outcomes (r = -.33). Technical troubleshooting was associated with greater positive outcomes (r = .17). Individual measuring higher on TAE are associated with increased positive outcomes with technology and decreased negative outcomes with technology.
Keywords: Cognitive Psychology; Adaptive Expertise; Technology; Scale Development